Investigation of the benefits of the oxazolidinium cation for plastic crystal and ionic liquid electrolytes - Sourjah, Azra; Kang, Colin S. M.; Ferrero Vallana, Federico M.; Hutt, Oliver E.; O’Dell, Luke A.; Pringle, Jennifer M. (Frontiers in Batteries and Electrochemistry, 2024)
Organic ionic plastic crystals (OIPCs) are promising for developing safer energy storage electrolytes. However, there remains a significant knowledge gap regarding how different cation-anion combinations influence their core properties, and cyclic ether-based cations have received limited attention. This study reports the synthesis and characterization of OIPCs based on the N-ethyl-Nmethyl-oxazolidinium cation [C2moxa] + and demonstrates the first instance of oxazolidinium OIPCs being combined with lithium salts to create electrolytes. The [C2moxa] + cation was paired with [FSI] -, [TFSI] -, [BF4] -, [PF6] -and [FTFSI] -anions. A study of the thermal, transport and electrochemical properties performed. Among the new salts developed, [C2moxa][BF4] exhibited the most promising characteristics, including the lowest entropy of melting (ΔS = 7 J mol -1 K -1 ), an extended phase I range (10 to 130 °C), the highest conductivity of 8 x 10 -6 S cm -1 at 30 °C, and an electrochemical stability window of 4.8 V. When the [C2moxa][BF4] and [C2moxa][FSI] were mixed with lithium salts (10, 20 and 50 mol% Li + ) of the same anion, the highest conductivity of 2 x 10 -3 S cm -1 at 30 °C was found for the 20 mol% LiFSI/[C2moxa][FSI] electrolyte. Finally, preliminary lithium plating/stripping experiments and coulombic efficiency (CE) measurements demonstrate stability for lithium cycling for all four [C2moxa] + electrolytes.